2019
DOI: 10.1111/jce.14080
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐guided second‐generation cryoballoon pulmonary vein isolation: Prospective comparison of the procedural and clinical outcomes with the conventional strategy

Abstract: Background: The utility of pressure waveform analyses to assess pulmonary vein (PV) occlusions has been reported in cryoballoon PV isolation (CB‐PVI) using first‐generation CBs. This prospective randomized study compared the procedural and clinical outcomes of pressure‐guided and conventional CB‐PVI. Methods and Results: Sixty patients with paroxysmal atrial fibrillation underwent CB‐PVI with 28‐mm second‐generation CBs. PV occlusions were assessed either by real‐time pressure waveforms without contrast utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…One method confirms leakage using an intracardiac echo Doppler, 128,129 and the other predicts the degree of occlusion from pressure changes and pressure waveforms by measuring the balloon tip pressure. [130][131][132] Although the benefits of bonus-freeze have not been evident since the launch of the 2nd-generation cryoballoon, it has been reported that bonus freezing prolongs both procedure time and fluoroscopy time, and increases complications. 133 The exposure dose is significantly reduced by changing from the conventional 2time bonus-freeze method to a 1-time method (single freeze).…”
Section: Reducing Radiation Exposurementioning
confidence: 99%
“…One method confirms leakage using an intracardiac echo Doppler, 128,129 and the other predicts the degree of occlusion from pressure changes and pressure waveforms by measuring the balloon tip pressure. [130][131][132] Although the benefits of bonus-freeze have not been evident since the launch of the 2nd-generation cryoballoon, it has been reported that bonus freezing prolongs both procedure time and fluoroscopy time, and increases complications. 133 The exposure dose is significantly reduced by changing from the conventional 2time bonus-freeze method to a 1-time method (single freeze).…”
Section: Reducing Radiation Exposurementioning
confidence: 99%
“…Technical measures consist of lowering fluoroscopy and cine frame rates, limited use of cine, lowering of the detector on the patient, collimation of region of interest, and avoidance of left anterior oblique projections [6,7]. Non-fluoroscopic measures are the use of ICE guidance, 3D CT overlay for PV anatomy, and real-time pressure waveforms to assess PV occlusion [7,[16][17][18]. Finally, using a novel angiography platform (e.g., Philips Azurion versus Allura system) can also reduce radiation exposure but this is not easily implemented [19].…”
Section: Reducing Radiation Exposurementioning
confidence: 99%
“…One method confirms leakage using an intracardiac echo Doppler, 128,129 and the other predicts the degree of occlusion from pressure changes and pressure waveforms by measuring the balloon tip pressure. [130][131][132] Although the benefits of bonus-freeze have not been evident since the launch of the 2nd-generation cryoballoon, it has been reported that bonus freezing prolongs both procedure time and fluoroscopy time, and increases complications. 133 The exposure dose is significantly reduced by changing from the conventional 2-time bonus-freeze method to a 1-time method (single freeze).…”
Section: Catheter Ablation 1 Reducing Radiation Exposurementioning
confidence: 99%